(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Vertebral artery syndrome is a condition associated with impaired conduction, manifested by signs of cerebrovascular insufficiency in the posterior part of the brain. Approximately 30% of cerebrovascular accidents causing transient ischemic attacks are associated with SPA. The disease often appears at a young age and reduces the ability to work. In addition, because it is progressive, it often leads to the development of transient ischemic attacks and even ischemic stroke.